Solution Structure of Mannobioses Unravelled by Means of Raman Optical Activity. Issue 5 (12th February 2019) - Pendrill, Robert; Mutter, Shaun T.; Mensch, Carl; Barron, Laurence D.; Blanch, Ewan W.; Popelier, Paul L. A.; Widmalm, Göran; Johannessen, Christian
Abstract: Structural analysis of carbohydrates is a complicated endeavour, due to the complexity and diversity of the samples at hand. Herein, we apply a combined computational and experimental approach, employing molecular dynamics (MD) and density functional theory (DFT) calculations together with NMR and Raman optical activity (ROA) measurements, in the structural study of three mannobiose disaccharides, consisting of two mannoses with varying glycosidic linkages. The disaccharide structures make up the scaffold of high mannose glycans and are therefore important targets for structural analysis. Based on the MD population analysis and NMR, the major conformers of each mannobiose were identified and used as input for DFT analysis. By systematically varying the solvent models used to describe water interacting with the molecules and applying overlap integral analysis to the resulting calculational ROA spectra, we found that a full quantum mechanical/molecular mechanical approach is required for an optimal calculation of the ROA parameters. Subsequent normal mode analysis of the predicted vibrational modes was attempted in order to identify possible marker bands for glycosidic linkages. However, the normal mode vibrations of the mannobioses are completely delocalised, presumably due to conformational flexibility in these compounds, rendering the identification of isolated marker bands unfeasible. Abstract : Solution Structure : Raman optical activity spectroscopy and comprehensive modelling reveals new insights into the building blocks of high‐mannose glycans.